1999
DOI: 10.1021/jp992193m
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Ion Association and Solvation in 2-Methoxyethanol:  Behavior of Tetraphenylarsonium, Picrate, and Tetraphenylborate Ions from Conductivity and Ultrasonic Data

Abstract: Precise measurements on electrical conductances and ultrasonic velocities of solutions of potassium picrate (KPic), potassium tetraphenylborate (KBPh 4 ), tetrabutylammonium tetraphenylborate (Bu 4 NBPh 4 ), and tetraphenylarsonium picrate (Ph 4 AsPic) in 2-methoxyethanol (ME) at temperatures 288.15 e T/K e 308.15 have been reported. The conductance data have been analyzed by the 1978 Fuoss conductance-concentration equation. Thermodynamics of the association processes have also been studied and the Coulombic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The compressibility behavior of solutes, which is the second derivative of the Gibbs energy, is a very sensitive indicator of molecular interactions and can provide useful information about this phenomenon [26][27][28]. The structural change of molecules takes place due to the existence of electrostatic field between interacting molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The compressibility behavior of solutes, which is the second derivative of the Gibbs energy, is a very sensitive indicator of molecular interactions and can provide useful information about this phenomenon [26][27][28]. The structural change of molecules takes place due to the existence of electrostatic field between interacting molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained equilibrium constants (K A ) for the ion-association reaction served to investigate the thermodynamics of this process. Consequently, the standard Gibbs energy ( G A ), the enthalpy ( H A ), and the entropy ( S A ) of the ion-association process were calculated according to the following equations [21][22][23]: …”
Section: Resultsmentioning
confidence: 99%
“…From Table 4, it was observed that, while the values of ΔS o for FeCl3 decreased with a increase in the temperature, for FeCl2, they indicated some disorder. The main factors which govern the standard entropy of ion association of electrolytes are (i) the size and shape of the ions, (ii) charge density on ions, (iii) electrostriction of the solvent molecules around the ions, and (iv) the penetration of the solvent molecules inside the space of the ions [34]. For both FeCl2 and FeCl3, ΔS o values indicated a decrease, as the composition of DMF in DMF-water mixed solvents increased.…”
Section: Thermodynamic Parametersmentioning
confidence: 99%